BODY CONCEPTS ON DEFICIENT PEOPLE BY STUDENTS: A REFLEXIVE ANALYSIS. (Fiep Bulletin - online, 2015)
We aimed to analyze the body concepts from students on people having any deficiency in an inclusive and non-inclusive context. The study was taken on students from the 8th years in public schools in Santa Maria, and involved two schools: one in the inclusive context, in which participated one class having deficient student included, and another class were not; and other school were there was no deficient student included, joining only one class. We used a form with semi-structured asks. Was identified that in all three classes, the importance of the body was related to well being, where the school having inclusion, well being was related to the concept of aesthetic and beauty standards. In the three classes the concept better punctuated on deficient people were positive, whereas students believed in the possibilities of success and happiness of this people, ins spite of their body resemblance. The class in which there was one included deficient student, body with deficiency was regarded with high relevance to ugly and imperfect body, what could be related to the fact that they see the limitations and difficulties their colleague faces daily. We conclude that body concepts here presented had positive interference in the inclusive context, because it was linked to factors beyond appearance/aesthetic, making worthy the person based upon the personality and attitudes, and considering that deficient people have the right to join the Physical Education as well as to practice general physical activities. Also, we highlight the need of Physical Education professionals to know the body concepts of their students, because they interfere in the classes, in practices and in the very same school inclusion.
Keywords: Body concepts; deficient people; school Physical Education.